Assessment of Some Hematological parameters Hemoglobin, White Blood Cells, and Platelets among Pregnant Women at Al-jemail Hospital, Western Libya - Elayadi Daw Mabrouk Elabed; Siddig Bushra Mohamed; Salih Abdelgadir Elmahdi Ahmed; Saeid Khalifa Sassi; Hussein Ali Khudheir Abood (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Pregnancy causes physiological changes that aid in the fetus's growth and get the mother ready for delivery. These adjustments are required to enhance the mother's and fetus's health. Objectives: The current study aims to evaluate the alterations in the level of hemoglobin, white blood cells, and platelets counts in pregnant women at Al-jemail Hospital. Libya. Methodology: A questionnaire was used to collect data from 73 pregnant women between the ages of 18 and 41 who were involved in a descriptive-analytical study at Al-Jemail General Hospital. The Sysmex blood analyzer was used to determine the Complete Blood Count (CBC) assay. Results: The study's findings demonstrated that pregnancy impacted blood components. Pregnant women's hemoglobin levels was insignificantly decreased p-vale (>0.050) at the means rate (10.19±1.37, 10.59±1.34, and 10.36±1.54) in 1st, 2nd, and 3rd trimesters of pregnancy, respectively. This resulted in reduction in hemoglobin levels that disseminated anemia and a higher rate of miscarriages among anemic women. To boost the immune system and get the body ready for delivery, the data also indicated that the rate of white blood cell count increased gradually across the trimesters of pregnancy and it is a significant difference p –value (0.000) at third trimester. To aid in the clotting process and prevent bleeding during delivery, also platelets progressively increased over time and also it is significant difference at second and third trimester p –vale (0.022, 0.001) respectively. Conclusion: It can be concluded that anemia during pregnancy may cause complications for the fetus, such as miscarriage or childbirth. Early pregnancy and the high rate of white blood cell counts increase gradually as the months of pregnancy increased (stages of pregnancy). The platelets were gradually increasing, reaching the highest count in the third stage of pregnancy. Moreover, our study emphasizes the need to increase attention to the health awareness of pregnant women during this sensitive period for the health of the mother and the fetus about the various physiological effects on blood components that our study found.